41 Cooper Union Square – save architecture, generative architecture - Wojtkiewicz, Sławomir (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2016)
One of the design criteria of generative design systems is multivariants, including all components of the design process. Another key factor to consider is the safety and human-friendly environment of space. Generative systems are advanced language development of solid geometry of the building, its functions and sustainable system of investigation into spatial solutions, in which a person is treated as a priority. Cooper Union building designed by Morphosis group, located in New York, is an outstanding example of achieving interesting form of spatial and functional system. The procedures generative design stage helped largely shape the space available, but in many cases supporting the physical condition of man. The article presents the scientific basis of the theory of generative used in the design of The Cooper Union Building for a sustainable environment and the architecture of intelligent not only in terms of aesthetic and functional, but the technology relating directly to the health of human attitudes – recipient designed space.